2022
DOI: 10.1007/s11060-022-04061-0
|View full text |Cite
|
Sign up to set email alerts
|

Management of neurofibromatosis type 2 and schwannomatosis associated peripheral and intraspinal schwannomas: influence of surgery, genetics, and localization

Abstract: Introduction Peripheral and intraspinal schwannomas are common and clinically complex pathologies in patients with Neurofibromatosis Type 2 (NF2) and Schwannomatosis (SWNT). Functional preservation and pain relief are the major goals in treating these tumors. Methods This retrospective observational study investigates the clinical and functional outcome of 205 operated peripheral (n = 148, 72%) and intraspinal (n = 57, 28%) schwannomas in 85 patients (53 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…There are no prospective studies on the use of a microscope to visualize nerve fibers intraoperatively, but according to expert opinions, this is recommended as a good practice point. Surgery is effective in pain management [ 135 ], especially in sporadic tumors [ 131 ]. Rates of complete resection depends on the presence of a genetic disorder (schwannomatosis or neurofibromatosis).…”
Section: Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…There are no prospective studies on the use of a microscope to visualize nerve fibers intraoperatively, but according to expert opinions, this is recommended as a good practice point. Surgery is effective in pain management [ 135 ], especially in sporadic tumors [ 131 ]. Rates of complete resection depends on the presence of a genetic disorder (schwannomatosis or neurofibromatosis).…”
Section: Surgerymentioning
confidence: 99%
“…Rates of complete resection depends on the presence of a genetic disorder (schwannomatosis or neurofibromatosis). In case of NF2, resection rates up to 82% are reported [ 135 ], whereas in spontaneous tumors, up to 92.5% may be achieved [ 133 ]. The risk for permanent or temporary new neurological deficits in benign lesions might be up to 15.2% [ 136 ].…”
Section: Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Hebert-Blouin et al 5,6 argued that NF2-associated peripheral nerve schwannomas are more difficult to resect and more likely to result in neurological deficit because of the higher rates of multinodular tumors with multifascicular involvement in NF2. Interestingly, Gugel et al 4 also observed lower rates of gross total resection in NF2-associated schwannomas compared with schwannomatosis-associated schwannomas (82% vs 93%, P = .030). Similarly, Safaee et al 7 also reported lower rates of gross total resection of NF2-associated schwannomas compared with sporadic tumors.…”
mentioning
confidence: 94%
“…Mehta et al 3 demonstrated that discreet modular tumors in patients with NF2 can be safely resected, with similar risks as sporadic schwannomas. Similarly, Gugel et al 4 reported on their experience of 205 tumors removed from 53 patients with NF2 and 32 patients with schwannomatosis. Again, they showed that resection of peripheral and intraspinal schwannomas is an effective and low-risk treatment options for patients afflicted with these genetic conditions.…”
mentioning
confidence: 95%